2024
DOI: 10.1002/iid3.1097
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intestinal flora in elderly Uygur patients with sarcopenia

Zimei Shan,
Na Cheng,
Jia Zhu
et al.

Abstract: ObjectiveThis study was designed to analyze the structural characteristics of the intestinal flora of elderly Uygur patients with sarcopenia, thereby providing new ideas for clinical treatment.MethodsFirstly, fecal samples were collected from 40 elderly Uygur patients with sarcopenia (Sarcopenia group) and 40 healthy people (Control group). Next, significant differences in the intestinal flora between the two groups were analyzed based on 16S rDNA high‐throughput sequencing. The linear discriminant analysis ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(72 reference statements)
0
0
0
Order By: Relevance
“…Compared to pathogen-free mouse skeletal muscle, germ-free mouse skeletal muscle showed atrophy [13]. The abnormality of intestinal flora in patients with sarcopenia is related to inflammatory response, and the composition of intestinal flora is significantly different from that of normal people [14]. More importantly, animal studies have found that transplantation of gut microbiota from pathogen-free mice to germ-free mice can increase skeletal muscle mass and reduce markers of muscle atrophy [13], and probiotic supplementation inhibited inflammatory signaling pathways such as NF-κB and improved muscle atrophy [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to pathogen-free mouse skeletal muscle, germ-free mouse skeletal muscle showed atrophy [13]. The abnormality of intestinal flora in patients with sarcopenia is related to inflammatory response, and the composition of intestinal flora is significantly different from that of normal people [14]. More importantly, animal studies have found that transplantation of gut microbiota from pathogen-free mice to germ-free mice can increase skeletal muscle mass and reduce markers of muscle atrophy [13], and probiotic supplementation inhibited inflammatory signaling pathways such as NF-κB and improved muscle atrophy [15,16].…”
Section: Introductionmentioning
confidence: 99%